Developing effective research proposals - Punch, Keith F. (London : Sage Publications Ltd., 2016)
This accessible, how-to guide can be used as a workbook to the author's 'An Introduction to Social Research', or as an independent guide. It is a guide to preparing a well-constructed research proposal, then presenting it effectively.
1. Introduction -- 2. Understanding Readers, Expectations and Functions -- 3. Including Ethics in Social Science Research Alis Oancea -- 4. Developing a General Framework for Proposals -- 5. Using Theory and Dealing with the Literature -- 6. Presenting Methods and Methodologies -- 7. Writing the Proposal -- 8. Getting Tactics Right -- 9. Examples of Proposals.
First edition published in 2000.
Includes bibliographical references (pages 178-182) and index.
Keywords: Proposal writing in the social sciences; Social sciences -- Methodology; Proposal writing in the social sciences; Social sciences -- Methodology